Relationship between running economy and kinematic parameters in long-distance runners - Pizzuto, F.; Fonseca de Oliveira, C.; Amorim Soares, T. S.; Rago, V.; Silva, G.; Oliveira, J. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to explore the relationship between running economy (RE) and sagittal, frontal, and transverse plane kinematic parameters in long-distance runners. A secondary purpose was to identify the kinematic predictors of RE during running at the lowest RE value, representing an individual's most efficient running intensity. Twenty recreational long-distance runners ran 3 submaximal stages on a treadmill (65, 75, and 85% of velocity at maximum oxygen consumption). Respiratory data were collected using a portable gas analysis system. Kinematics were gathered using passive retroreflective markers and 8 high-resolution infrared cameras to collect the respective trajectories. Hip, knee, and ankle angles at foot strike and stance phase, as well as spatio-temporal parameters were calculated during each gait cycle. Knee flexion/extension range of motion (ROM), knee ab/adduction ROM, and hip ab/adduction ROM during the stance phase of the gait cycle showed positive moderate to large correlations with RE (r ± 90% confidence intervals = 0.51 ± 0.29; 0.49 ± 0.30; 0.53 ± 0.28, respectively). Knee and hip ab/adduction ROMs during the stance phase are predictors of RE, accounting for 44% of RE variance. Therefore, sagittal and frontal plane kinematics affect RE-inducing alterations in running performance. Coaches, athletic trainers, and anyone involved in running training prescription should consider a relationship between these parameters to ensure optimal technique and, consequently, to improve RE in recreational long-distance runners.